2015
DOI: 10.1589/jpts.27.1951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air stacking on pulmonary function and peak cough flow in patients with cervical spinal cord injury

Abstract: [Purpose] This study evaluated the effects of air stacking on pulmonary function and peak cough flow in patients with cervical spinal cord injury. [Subjects] Twenty-six patients were included in the study and were randomized into experimental (n = 14) and control (n = 12) groups. [Methods] Both groups performed therapeutic exercises: the control group performed incentive spirometry, while the experimental group performed 20 repetitions of air stacking exercise twice a day. The training for both groups continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The results of this study showed that pulmonary function was significantly improved in the AST group (p<0.05), and the mean change was significantly higher in the AST group than the IST group. These results are consistent with the findings of previous studies, which have significantly increased FVC after AST training in CSCI patients [25,26]. Neuromuscular disease patients with respiratory muscles weakness cannot breathe deeply.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that pulmonary function was significantly improved in the AST group (p<0.05), and the mean change was significantly higher in the AST group than the IST group. These results are consistent with the findings of previous studies, which have significantly increased FVC after AST training in CSCI patients [25,26]. Neuromuscular disease patients with respiratory muscles weakness cannot breathe deeply.…”
Section: Discussionsupporting
confidence: 93%
“…After intervention, FVC and PCF were found to have increased significantly more in the experimental group than in the control group, and in the experimental group, PCF increased by 27.3% (Jeong and Yoo, 2015). These results are in accord with our results.…”
Section: ⅳ Discussionsupporting
confidence: 92%
“…In other studies undertaken to evaluate the effects of air stacking on pulmonary function and peak cough flow in patients with cervical spinal cord injury, air stacking exercise for 6 weeks significantly improved pulmonary function and peak cough flow (Jeong and Yoo, 2015).…”
mentioning
confidence: 88%
“…Some of the benefits of LVR include slowing the progression of pulmonary decline in individuals with neurodegenerative disease and increasing vital capacity. [37][38][39][40][41] Any form of breath stacking may help to increase respiratory support for speech by making it possible to speak louder and/or longer. 26,42 Breath stacking can be accomplished in different ways.…”
Section: Breath Stacking and Lung Volume Recruitmentmentioning
confidence: 99%